Fatigue strength evaluation of PPGF35 by energy approach during mechanical tests (Fracture and Structural Integrity, 2021)
Thanks to the progress of research on thermoplastic materials, the properties of composite materials have improved considerably.The aim of this study is the evaluation of fatigue strength of glass-fibre-reinforced polypropylene composite (PPGF35) by applying both the Risitano Thermographic Method (RTM) and the new Static Thermographic Method (STM).
Keywords: Glass-fibre-reinforced polypropylene composite; Fatigue assessment; Risitano Thermographic Method; Static Thermographic Method